Case report: Novel compound heterozygosity for pathogenic variants in MED23 in a syndromic patient with postnatal microcephaly - Salzano, Emanuela; Niceta, Marcello; Pizzi, Simone; Radio, Francesca Clementina; Busè, Martina; Mercadante, Francesca; Barresi, Sabina; Ferrara, Arturo; Mancini, Cecilia; Tartaglia, Marco; Piccione, Maria (Frontiers in Neurology, 2023)
Biallelic loss-of-function variants in MED23 cause a recessive syndromic intellectual disability condition with or without epilepsy (MRT18). Due to the small number of reported individuals, the clinical phenotype of the disorder has not fully delineated yet, and the spectrum and frequency of neurologic features have not been fully characterized. Here we report a 5-year-old girl with compound heterozygous for two additional MED23 variants. Beside global developmental delay, axial hypotonia and peripheral increased muscular tone, absent speech, generalized tonic seizures, which fit well MRT18, occurrence of post-natal progressive microcephaly has been here documented. Retrospective assessment of the previously reported clinical data for these subjects confirms occurrence of post-natal progressive microcephaly as a previously unappreciated feature of the phenotype of MED23-related disorder.